2006
DOI: 10.1002/ijc.21824
|View full text |Cite
|
Sign up to set email alerts
|

SAHA‐sensitized prostate cancer cells to TNFα‐related apoptosis‐inducing ligand (TRAIL): Mechanisms leading to synergistic apoptosis

Abstract: Treatment of cancer cells with histone deacetylase inhibitors (HDACi) such as suberolylanilide hydroxamic acid (SAHA) activates genes that promote apoptosis. To enhance proapoptotic efficiency, SAHA has been used in combination with radiation, kinase inhibitors and cytotoxic drugs. Although several prostate cells respond to TNFα‐Related Apoptosis‐Inducing Ligand (TRAIL), LNCaP are resistant. This model system was utilized to examine the advantages of combined treatment with SAHA and TRAIL. In LNCaP cells, TRAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…LNCaP cells are known to be refractory to apoptosis induction by TRAIL (Deeb et al, 2004;Yamaguchi et al, 2005;Hu et al, 2006;Lakshmikanthan et al, 2006). We confirmed this in a dose-escalation experiment ( Figure 1a) and observed that LNCaP cells were refractory to TRAIL-induced cell death to a dose as high as 150 ng ml À1 while in PC3 cells 10 ng ml À1 TRAIL treatment resulted in about 70% inhibition of cell growth.…”
Section: Egcg Sensitizes Lncap Cells To Trail-mediated Cell Growth Insupporting
confidence: 81%
“…LNCaP cells are known to be refractory to apoptosis induction by TRAIL (Deeb et al, 2004;Yamaguchi et al, 2005;Hu et al, 2006;Lakshmikanthan et al, 2006). We confirmed this in a dose-escalation experiment ( Figure 1a) and observed that LNCaP cells were refractory to TRAIL-induced cell death to a dose as high as 150 ng ml À1 while in PC3 cells 10 ng ml À1 TRAIL treatment resulted in about 70% inhibition of cell growth.…”
Section: Egcg Sensitizes Lncap Cells To Trail-mediated Cell Growth Insupporting
confidence: 81%
“…TRAIL is an effective apoptotic agent by itself or in combination with other apoptotic drugs. We have shown synergistic increase in apoptotic response when TRAIL was combined with antiprogestin mifepristone (43) or by inhibiting the function of heat shock protein 90 (27,34), inhibiting the proteasomal activity (34), or treatment with histone deacetylase inhibitor, SAHA (25). Our present results show that treatment with both TRAIL and CGP Figure 3.…”
Section: Discussionmentioning
confidence: 52%
“…In some cells, caspase-8 propagates death signal directly through the activation of procaspase-3, whereas in others, the apoptotic signal is amplified via the mitochondria. In the latter, caspase-8 cleaves Bid, which translocates into the mitochondria and initiates changes in the mitochondria leading to the release of cytochrome c. Bid, a member of the BH3 domain only subgroup of Bcl 2 family proteins, is a 22-kDa cytosolic protein that is cleaved by activated caspase-8 in cells treated with variety of apoptotic agents, such as TRAIL (24), histone deacetylase inhibitor (25), and UV radiation (26). The truncated 15-kDa Bid (tBid) is translocated into the mitochondria, where it participates in changes leading to the release of cytochrome c to the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study provides compelling evidence that although HDACi can indeed induce expression of TRAIL and/or its cognate receptors, this event is not necessary to mediate synergistic apoptosis of target cells by using a combination of HDACi and recombinant TRAIL or anti-DR4/DR5 mAbs (33). Other studies have correlated synergistic tumor cell apoptosis by HDACi and activators of the TRAIL pathway with decreased expression of c-FLIP (8,25), decreased expression of apoptosis inhibitors and Bcl-2 (25), inhibition of Cdc2 protein and subsequent down-regulation of survivin and XIAP (26), and modulation of NF-B activity (28,34,35). It is not yet clear whether a common molecular event will be identified as being requisite to mediate synergistic apoptosis by HDACi and TRAIL activators, or whether the responses will depend on the cell type and/or HDACi under investigation.…”
Section: Discussionmentioning
confidence: 99%